Immune cell expression patterns of CD39/CD73 ectonucleotidases in rodent models of cardiac arrest and resuscitation - Aoki, Tomoaki; Wong, Vanessa; Yin, Tai; Nakamura, Eriko; Endo, Yusuke; Hayashida, Kei; Robson, Simon C.; Nandurkar, Harshal; Diamond, Betty; Kim, Sun Jung; Murao, Atsushi; Wang, Ping; et al. (Frontiers in Immunology, 2024)
Background Cardiac arrest (CA) is a significant public health concern. There is the high imminent mortality and survival in those who are resuscitated is substantively compromised by the post-CA syndrome (PCAS), characterized by multiorgan ischemia–reperfusion injury (IRI). The inflammatory response in PCAS is complex and involves various immune cell types, including lymphocytes and myeloid cells that have been shown to exacerbate organ IRI, such as myocardial infarction. Purinergic signaling, as regulated by CD39 and CD73, has emerged as centrally important in the context of organ-specific IRI. Hence, comprehensive understanding of such purinergic responses may be likewise imperative for improving outcomes in PCAS. Methods We have investigated alterations of immune cell populations after CA by utilizing rodent models of PCAS. Blood and spleen were collected after CA and resuscitation and underwent flow cytometry analysis to evaluate shifts in CD3+CD4+ helper T cells, CD3+CD8a+ cytotoxic T cells, and CD4/CD8a ratios. We then examined the expression of CD39 and CD73 across diverse cell types, including myeloid cells, T lymphocytes, and B lymphocytes. Results In both rat and mouse models, there were significant increases in the frequency of CD3+CD4+ T lymphocytes in PCAS (rat, P < 0.01; mouse, P < 0.001), with consequently elevated CD4/CD8a ratios in whole blood (both, P < 0.001). Moreover, CD39 and CD73 expression on blood leukocytes were markedly increased (rat, P < 0.05; mouse, P < 0.01 at 24h). Further analysis in the experimental mouse model revealed that CD11b+ myeloid cells, with significant increase in their population (P < 0.01), had high level of CD39 (88.80 ± 2.05 %) and increased expression of CD73 (P < 0.05). CD19+ B lymphocytes showed slight increases of CD39 (P < 0.05 at 2h) and CD73 (P < 0.05 at 2h), while, CD3+ T lymphocytes had decreased levels of them. These findings suggested a distinct patterns of expression of CD39 and CD73 in these specific immune cell populations after CA. Conclusions These data have provided comprehensive insights into the immune response after CA, highlighting high-level expressions of CD39 and CD73 in myeloid cells.